Residual stenosis >30% is an independent predictor of stroke recurrence postendovascular therapy in patients with symptomatic intracranial atherosclerotic stenosis - Jing Liu; Yuchuan Ding; Zhe Cheng; Jie Gao; Fenghai Li; Qianhui Zhao; Xiaokun Geng (Environmental Disease)
Objective: The purpose of this study was to investigate the correlation between residual stenosis rate following percutaneous transluminal angioplasty and stenting (PTAS) and the incidence of ischemic stroke recurrence in patients with symptomatic intracranial atherosclerotic stenosis (sICAS) within 1-year postsurgery. Subjects and Methods: We retrospectively analyzed data from 113 patients with sICAS treated with PTAS between January 1, 2018 and March 31, 2022, at the Stroke Intervention and Translational Center in Beijing Luhe Hospital, Capital Medical University. Outcomes were included stroke and death after stenting within 1 year. Of the sample, 60 patients had middle cerebral artery (MCA) or basilar artery (BA) lesion, and 53 patients had internal carotid artery (ICA) or vertebral artery (VA) lesion. Logistic regression evaluated the association between residual stenosis rate and clinical outcomes. Results: The occurrence rate of perioperative endpoint events was 5.3%. The 3-month rate of endpoint event was 8.8%. A total of 16 endpoint events (14.2%) were observed within a 1-year timeframe. The residual stenosis rate >30% (odds ratio [OR] 3.95; 95% confidence interval [CI]: 1.01–15.38; P = 0.048) and MCA or BA lesion (OR 3.85; 95% CI 1.00–14.89; P = 0.050) independently correlated with ischemic events within 1 year. In the MCA+BA group, residual stenosis rate >30% was observed tended to increase the occurrence of ischemic events within 1 year (OR: 3.35; 95% CI: 0.86–13.10; P = 0.083) after accounting for other confounders. In the ICA+VA group, univariate analysis showed residual stenosis >30% was associated with ischemic events within 1 year (P = 0.028), but no independent association was found after adjusting for other confounding factors. Conclusions: Residual stenosis rate >30% is an independent predictor of stroke recurrence at 1-year postendovascular therapy in patients with sICAS.